Effect of delayed palivizumab administration on respiratory syncytial virus infection-related hospitalisation: A retrospective, observational study. Issue 47 (24th November 2021) - Kamori, Akiko; Morooka, Yuya; Yamamura, Kenichiro; Chong, Pin Fee; Kuga, Noriko; Takahata, Yasushi; Sagawa, Koichi; Furuno, Kenji
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Respiratory syncytial virus (RSV) infection is an important cause of hospitalization in infants and young children. Monthly administration of palivizumab during the RSV season is effective in preventing severe infections in children with comorbidities. However, determining the onset of the RSV season for starting palivizumab is often challenging. The present study aimed to evaluate the ideal timing to start palivizumab and its effect on hospitalization in the real world. We performed a retrospective, observational study to identify the relationship between the timing of the first dose of palivizumab administration and RSV-related hospitalization. Medical records from 2015 to 2019 were reviewed. We included patients who had indications for palivizumab as of July 1 in each year. We counted the proportion of children receiving palivizumab and the number of RSV infection-related hospitalizations each month. We also evaluated the differences in background and underlying disease between children with and without hospitalization. A total of 498 patients were included, and 105 (21.0%) completed the first dose in July when the RSV season usually begins in Japan. Twenty-three (4.6%) patients were hospitalized for RSV infection during the observation period, with 13 (56.5%) hospitalizations before their first dose of palivizumab. The remaining 10 patients were hospitalized after receiving 1 or more doses of palivizumab. Children living with siblings and children with cyanosis originating from congenital heart disease had a higher risk of RSV with odds ratios of 5.1 (95% confidence interval 1.48-17.6, P < .01) and 3.3 (95% confidence interval 1.33-7.94, P < .01), respectively. Delays in administering palivizumab at the beginning of the season increases the rate of RSV infection-related hospitalization. To maximize prophylactic effectiveness, administering the first dose as early as possible in the RSV season is crucial, with priority for cyanotic children or those with siblings.